STUDENTS’ AWARENESS TOWARD 21ST CENTURY SKILLS - Khilda Shopia; Aslamiyah, Sarah; Isnaniah; Syifa Fadhilah Hamid; Purnawati; Muhamad Rizky Fadhil (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2024)
Understanding 21st-century abilities is essential for students to succeed in the quickly changing digital and information age. These abilities, which are divided into learning, literacy, and life skills categories, include vital proficiencies including critical thinking, creativity, teamwork, communication, information literacy, and flexibility. In order to successfully handle societal difficulties, this study looks at how well students comprehend and apply these abilities. The results show that although students show a moderate level of knowledge regarding digital literacy and teamwork, deficiencies in critical thinking, problem-solving, and leadership abilities still exist. The design of the curriculum, teacher participation, and availability of digital tools are some of the factors that affect awareness. Incorporating 21st-century skills into teaching methods through competency-based assessments, technological integration, and experiential learning is necessary to raise awareness. Thus, it can emphasize how critical it is to develop these abilities in order to equip pupils for both societal and lifetime learning.